The Biological Activities of Endemic Ballota pseudodictamnus subsp. lycia. - RAYAMAN, ERKAN; TAŞKIN, TURGUT (My University, 2022)
The genus Ballota L. (Lamiaceae) includes species known as boz ot, bal otu, nemnem otu and have medicinal uses among the people. Additionally, it known to be used by the public in the treatment of cough, asthma, headache, nausea, hemorrhoids, wounds and burns. Ballota taxa have various phytochemical classes such as essential oils, iridoids, saponins, terpenoids, flavonoids, phenolic acids, tannins, and organic acids. Ballota pseudodictamnus subsp. lycia is one of the endemic species growing in southwestern Turkey. As a result of our research on the literature a limited number of studies have been found on the biological activities of this species. The aim of this study is to examine the antioxidant, antimicrobial, anticholinesterase and anti-urease activities of different extracts (petroleum ether, chloroform and methanol) obtained from the aerial part of B. pseudodictamnus subsp. lycia. DPPH, CUPRAC, and FRAP techniques were used to examine the antioxidant properties of plant\" extracts. The extracts\" anti-urease, anticholinesterase and antimicrobial activity were determined using the Indophenol, Ellman and agar well diffusion method techniques, respectively. While the petroleum ether extract obtained from plant, was found to be effective against S. aureus, S.epidermidis and E. faecalis strains; its chloroform extract was effective against S.aureus and S.epidermidis strains and its methanol extract was found to be effective against Acinetobacter baumannii strains. It was found that the plant’ methanol extract showed the highest antioxidant activity when compared to the other extracts.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Ballota pseudodictamnus subsp. lycia; antioxidant activity; antimicrobial activity; enzyme inhibition